Isolation and Characterization of Plantaricin Produced by Lactobacillus plantarum Strains (IIA-1A5, IIA-1B1, IIA-2B2) - I I Arief; . Jakaria; T Suryati; Z Wulandari; E Andreas (Faculty of Animal Science, Bogor Agricultural University, 2013)
Bacteriocins produced by Indonesian lactic acid bacteria Lactobacillus plantarum IIA-1A5, IIA-1B1, IIA-2B2 were purified and characterized. Plantaricin W gene had been successfully amplified from all strains. This amplicon showed the expected 200 bp size of plantaricin W gene. This bacteriocins purified from L. plantarum IIA-1A5, IIA-1B1, and IIA-2B2 were named plantaricin IIA-1A5, IIA-1B1, and IIA-2B2. Purification by cation exchange chromatography increased the purity (fold) and activity of plantaricins. Purity of plantaricin IIA-1A5 was increased by 3.13 fold with specific activity 13.40 AU/mg. Plantaricin IIA-1B1 had 2.98 fold purity with specific activity 5.12 AU/mg, while purity of plantaricin IIA-2B2 was 1.37 fold with specific activity 7.70 AU/mg. All plantaricins could inhibit the growth of pathogenic bacteria, such as Escherichia coli, Salmonella typhimurium, Bacillus cereus, and Staphylococcus aureus. Plantaricins could be digested by trypsin. Stability of plantaricins at 80 oC for 30 min and at 121 oC for 15 min were affected by type of plantaricin and species of pathogenic bacteria. Generally, plantaricin IIA-1A5 was better as antimicrobial agent than plantaricin IIA-1B1 and plantaricin IIA-2B2.